Coexistence of Dominant Marine Phytoplankton Sustained by Nutrient Specialization - Takako Masuda; Keisuke Inomura; Jan Mareš; Taketoshi Kodama; Takuhei Shiozaki; Takato Matsui; Koji Suzuki; Shigenobu Takeda; Curtis Deutsch; Ondřej Prášil; Ken Furuya (Microbiology Spectrum, 2023)
ABSTRACT Prochlorococcus and Synechococcus are the two dominant picocyanobacteria in the low-nutrient surface waters of the subtropical ocean, but the basis for their coexistence has not been quantitatively demonstrated. Here, we combine in situ microcosm experiments and an ecological model to show that this coexistence can be sustained by specialization in the uptake of distinct nitrogen (N) substrates at low-level concentrations that prevail in subtropical environments. In field incubations, the response of both Prochlorococcus and Synechococcus to nanomolar N amendments demonstrates N limitation of growth in both populations. However, Prochlorococcus showed a higher affinity to ammonium, whereas Synechococcus was more adapted to nitrate uptake. A simple ecological model demonstrates that the differential nutrient preference inferred from field experiments with these genera may sustain their coexistence. It also predicts that as the supply of NO3− decreases, as expected under climate warming, the dominant genera should undergo a nonlinear shift from Synechococcus to Prochlorococcus, a pattern that is supported by subtropical field observations. Our study suggests that the evolution of differential nutrient affinities is an important mechanism for sustaining the coexistence of genera and that climate change is likely to shift the relative abundance of the dominant plankton genera in the largest biomes in the ocean. IMPORTANCE Our manuscript addresses the following fundamental question in microbial ecology: how do different plankton using the same essential nutrients coexist? Prochlorococcus and Synechococcus are the two dominant picocyanobacteria in the low-nutrient surface waters of the subtropical ocean, which support a significant amount of marine primary production. The geographical distributions of these two organisms are largely overlapping, but the basis for their coexistence in these biomes remains unclear. In this study, we combined in situ microcosm experiments and an ecosystem model to show that the coexistence of these two organisms can arise from specialization in the uptake of distinct nitrogen substrates; Prochlorococcus prefers ammonium, whereas Synechococcus prefers nitrate when these nutrients exist at low concentrations. Our framework can be used for simulating and predicting the coexistence in the future ocean and may provide hints toward understanding other similar types of coexistence.